Thyroiditis is the most commonly encountered autoimmune disease worldwide. (Homoeopathy for All, 2023)
Thyroiditis is a general term for  inflammation of the thyroid gland,  and it can be associated with  thyroid dysfunction. Thyroiditis is  classified according to clinical  symptoms (painful or painless),  onset of symptoms (acute,  subacute, chronic), and underlying  etiology (autoimmunity, infection,  drugs, radiation). The most  common forms of thyroiditis  include Hashimoto, postpartum,  and subacute. Most forms of  thyroiditis result in a triphasic  disease pattern of thyroid  dysfunction. Patients will have an  initial phase of hyperthyroidism  (thyrotoxicosis) attributed to the  release of preformed thyroid  hormone from damaged thyroid  cells. This is followed by  hypothyroidism, when the thyroid  stores are depleted, and then  eventual restoration of normal  thyroid function. Some patients  m a y d e v e l o p p e r m a n e n t  hypothyroidism.
Keywords: thyrotoxicosis; hypothyroidism